Fuzzy Logic Based Speed Control of a Five-Phase Series Connected Two-Motor Drive System Fed from SVPWM VSI - Abdalla, Turki Y.; Abbas, Abbas H.; Hairik, Haroutuon A.; Thejel, Rabee' H. (Basrah Journal for Engineering Sciences, 2010)
A five-phase two-motor drive system with a series connection of stator windings and decoupled dynamic control is considered in the present paper. The two-motor drive system is supplied from a single five-phase Space Vector Pulse Width Modulation (S VPWM) Voltage Source Inverter (VSI) and controlled using a vector control scheme, provided that the stator windings are connected in series with appropriate phase transposition. The concept has been developed under the assumption that the inverter voltages are controlled in the stationary dq-reference frame. A fuzzy logic-based speed controller has been constructed and used to drive the two-motor in this work. The two-motor system, inverter system, and fuzzy controller models are implemented and tested using Simulink/Matlab facilities. 1be presented results show the validity of the model to do well for the sake of speed control in wider different operating conditions.